Near real time vehicle tracking using GIS - Joshi, Nilakshi; Tripathy, Amiya Kumar; Sawant, Suryakant; Patel, Tanvi; Waghmare, Sailee; Clusher, Blessy (2015 International Conference on Technologies for Sustainable Development (ICTSD), 2015)
The Traffic problems are a critical problem that influences the travel time of the vehicles. The critical road conditions affecting the smooth movement of vehicles increases the traffic issue also the unorganized traffic flow, no dividers, steep curves, etc. gives birth to the accidents. Lack of information of the shortest path affects the emergency vehicle routing. Although calamities, accidents or casualties are subject to factors that cannot be predetermined, an precautionary measures can play a crucial role to avoid the same. The aim of this work is to develop a GIS based system for efficient vehicle management. GPS on client side gets coordinates of the client and sends it to the web server. The Server handles the request and updates the database with the locations of all the vehicles. The information is plotted on a GIS MAP and viewed by the admin to guide the user. By using the information obtained from the client; client can be routed to the most efficient path, he can also be updated with the accident prone areas. In this system dynamic shortest path is used for efficient travelling. The algorithm used for shortest path is based on Dijkstra algorithm. This data can be further exported in the form of daily reports. Using Geo Fencing concepts, alerts are sent to the client, when a client diverts from his routed path. This paper explores the foundation of GIS-GPS, location based services and Geo Fencing.